pH-Responsive Starch-Citrate Nanoparticles for Controlled Release of Paracetamol - Chin, Suk Fun; Ain Nadirah, Romainor; Pang, Suh Cem; Lee, Book Kiat; Hwang, Siaw San (John Wiley & Sons, Inc, 2019)
Starch-citrate samples with degrees of substitution (DS) ranging from 0.11 to 0.90 are synthesized by a green esterification reaction between citric acid and native sago starch (Metroxylon sagu) in an aqueous medium. Starch-citrate nanoparticles with mean diameter of 105 nm are subsequently obtained by controlled precipitation through drop-wise addition of dissolved starch-citrate solution into excess absolute ethanol. These nanoparticles are observed to exhibit pH-responsive release profiles within the physiological pH range of 1.2–8.6. The release profile of a model drug (paracetamol) is observed to obey the zero-order kinetics, with the release mechanism based on the diffusion and swelling model. The cytotoxicity study in HaCaT cell lines (human skin cells) shows that starch-citrate nanoparticles are non-toxic and hence are suitable for biomedical applications as pH-responsive drug carriers.